Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast

Enzymatic hydrolysis and ethanol production using xyloglucanase and debaromyces hansenii from tamarind kernel powder: galactoxyloglucan predominant hemicellulose - Menon, Vishnu; Prakash, Gyan; Rao, Mala (Journal of Biotechnology, 2010)
The hydrolysis and ethanol production from tamarind kernel powder (TKP), a rich source of galactoxyloglucan (GXG) was investigated for the first time using xyloglucanase and thermotolerant Debaromyces hansenii. The acid hydrolysis of TKP with 2N H(2)SO(4) at 120 degrees C for 30 min yielded an overall saccharification of 94% based on the total available carbohydrate content and further fermentation at 40 degrees C with thermotolerant D hansenii produced an ethanol yield of 0.35 g/g. A maximum hydrolysis of 55 and 78% for GXG was obtained in 48 h at 50 degrees C using Thermomonospora xyloglucanase (TXy) and accellerase (TM) 1000, respectively. The synergistic effect of beta-galactosidase and xyloglucanase was demonstrated by the exogenous addition of beta-galactosidase to TXy which improved the overall hydrolysis of GXG by 30%. The rate of hydrolysis of GXG with TXy and accellerase was increased by 15-20% in the presence of chemical surfactants (tween 80 and toluene) or protein additive (BSA). The fermentation of enzymatic hydrolysates of GXG by TXy and accellerase with free cells at 40 degrees C produced an ethanol yield of 0.39 and 0.41 g/g whereas with immobilized cells produced 0.45 and 0.43 g/g, respectively, with a theoretical conversion efficiencies of 78-88%. The immobilized yeast cells were reused six times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Galactoxyloglucan; Hydrolysis; Tamarind kernel powder; Thermotolerant yeast; Xyloglucanase

Bioethanol production from renewable polymer lichenan using lichenase from an alkalothermophilic thermomonospora sp and thermotolerant yeast - Menon, Vishnu; Divate, Rupesh; Rao, Mala (Fuel Processing Technology, 2011)
Biomass feedstocks available decentrally will be more commodious for localized biorefinery approach than the exhaustive large scale and centralized plants driven by cost intensive technology. Lichen is present in a wide range of habitats in a distributed manner. A maximum hydrolysis of 73%-76% for lichenan from Cetraria islandica, Usnea barbata and Parmelia sp. were obtained in 24 h using lichenase from an alkalothermophilic Thermomonospora sp. wherein the hydrolysis was 100% with commercial enzyme Accellerase (TM) 1000. The synergistic role of beta-glucosidase in lichenan hydrolysis was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora lichenase which resulted in complete hydrolysis. The hydrolysates of lichenan obtained using Accellerase or a cocktail of Thermomonospora lichenase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.45 g/g-0.48 g/g with theoretical conversion efficiencies of 93%-96%. The Ca-alginate immobilized yeast cells were reused eight times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrolysis; Lichenan; Lichenase; Synergism; Thermotolerant yeast

Biochemical characterization of a novel thermostable xyloglucanase from an alkalothermophilic thermomonospora sp. - Pol, Dipali; Menon, Vishnu; Rao, Mala (Extremophiles, 2012)
Xyloglucanase from an extracellular culture filtrate of alkalothermophilic Thermomonospora sp. was purified to homogeneity with a molecular weight of 144 kDa as determined by SDS-PAGE and exhibited specificity towards xyloglucan with apparent K (m) of 1.67 mg/ml. The enzyme was active at a broad range of pH (5-8) and temperatures (40-80A degrees C). The optimum pH and temperature were 7 and 70A degrees C, respectively. The enzyme retained 100% activity at 50A degrees C for 60 h with half-lives of 14 h, 6 h and 7 min at 60, 70 and 80A degrees C, respectively. The kinetics of thermal denaturation revealed that the inactivation at 80A degrees C is due to unfolding of the enzyme as evidenced by the distinct red shift in the wavelength maximum of the fluorescence profile. Xyloglucanase activity was positively modulated in the presence of Zn2+, K+, cysteine, beta-mercaptoethanol and polyols. Thermostability was enhanced in the presence of additives (polyols and glycine) at 80A degrees C. A hydrolysis of 55% for galactoxyloglucan (GXG) from tamarind kernel powder (TKP) was obtained in 12 h at 60A degrees C and 6 h at 70A degrees C using thermostable xyloglucanases, favouring a reduction in process time and enzyme dosage. The enzyme was stable in the presence of commercial detergents (Ariel), indicating its potential as an additive to laundry detergents.
Keywords: Alkalothermophilic Thermomonospora sp.; Biotechnological applications; Purification; Thermostable; Xyloglucanase

Inhibition of xyloglucanase from an alkalothermophilic thermomonospora sp by a peptidic aspartic protease inhibitor from Penicillium sp VM24 - Menon, Vishnu; Rao, Mala (Bioresource Technology, 2012)
A bifunctional inhibitor from Penicilliurn sp VM24 causing inactivation of xyloglucanase from Thermomonospora sp and an aspartic protease from Aspergillus saitoi was identified. Steady state kinetics studies of xyloglucanase and the inhibitor revealed an irreversible, non-competitive, two-step inhibition mechanism with IC50 and K-i; values of 780 and 500 nM respectively. The interaction of o-phthalaldehyde (OPTA)-labeled xyloglucanase with the inhibitor revealed that the inhibitor binds to the active site of the enzyme. Far- and near-UV spectrophotometric analysis suggests that the conformational changes induced in xyloglucanase by the inhibitor may be due to irreversible denaturation of enzyme. The bifunctional inhibitor may have potential as a biocontrol agent for the protection of plants against phytopathogenic fungi. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aspartic protease; Bifunctional inhibitor; Biocontrol agent; Inactivation mechanism; Xyloglucanase

Low-molecular-mass aspartic protease inhibitor from a novel penicillium sp.: implications in combating fungal infections - Menon, Vishnu; Rao, Mala (Microbiology-SGM, 2012)
A low-molecular-mass aspartic protease inhibitor was isolated from a novel Penicillium sp. The inhibitor was purified to homogeneity, as shown by reversed-phase HPLC and SDS-PAGE. The M-r of the inhibitor was 1585 and the amino acid composition showed the presence of D, D, D, E, A, K, L, Y, H, I and W residues. The steady-state kinetic interactions of Aspergillus saitoi aspartic protease with the inhibitor revealed the reversible, competitive, time-dependent tight-binding nature of the inhibitor, with IC50 and K-i values of 1.8 and 0.85 mu M, respectively. Fluorescence spectroscopy and circular dichroism analysis showed that inactivation of the enzyme was due to binding of the inhibitor to the active site. The inhibitor was found to inhibit mycelial growth and spore germination of Aspergillus fumigatus and Aspergillus niger in vitro with MIC values of 1.65 and 0.30 mu g ml(-1), respectively. This study will potentially open the way towards the development of a tight-binding peptidic inhibitor against fungal aspartic proteases to combat human fungal infections.

Slow-tight binding inhibition of pepsin by an aspartic protease inhibitor from streptomyces sp MBR04 - Menon, Vishnu; Rao, Mala (International Journal of Biological Macromolecules, 2012)
The present article reports a low molecular weight aspartic protease inhibitor from a Streptomyces sp. MBR04 exhibiting a two-step inhibition mechanism against pepsin. The kinetic interactions revealed a reversible, competitive, slow-tight binding inhibition with an IC50 and K-i values of 4.5 nM and 4 nM respectively. The conformational changes induced upon inhibitor binding to pepsin was monitored by far and near UV analysis, demonstrated that the inhibitor binds to the active site and causes inactivation. Chemical modification of the inhibitor with WRK and TNBS abolished the antiproteolytic activity of the inhibitor. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Aspartic protease inhibitor; Low molecular weight; Slow-tight binding inhibition

Trends in bioconversion of lignocellulose: biofuels, platform chemicals & biorefinery concept - Menon, Vishnu; Rao, Mala (Progress in Energy and Combustion Science, 2012)
Bioconversion of renewable lignocellulosic biomass to biofuel and value added products are globally gaining significant prominence. Market forces demonstrate a drive towards products benign to natural environment increasing the importance of renewable materials. The development of second generation bioethanol from lignocellulosic biomass serves many advantages from both energy and environmental point of views. Biomass an inexpensive feedstock considered sustainable and renewable, is an option with the potential to replace a wide diversity of fossil based products within the energy sector; heat, power, fuels, materials and chemicals. Lignocellulose is a major structural component of woody and non-woody plants and consists of cellulose, hemicellulose and lignin. The effective utilization of all the three components would play a significant role in the economic viability of cellulosic ethanol. Biomass conversion process involves five major steps, choice of suitable biomass, effective pretreatment, production of saccharolytic enzymes-cellulases and hemicellulases, fermentation of hexoses and pentoses and downstream processing. Within the context of production of fuels from biomass, pretreatment has come to denote processes by which cellulosic biomass is made amenable to the action of hydrolytic enzymes. The limited effectiveness of current enzymatic process on lignocellulose is thought to be due to the relative difficulties in pretreating the feedstocks. The present review is a comprehensive state of the art describing the advancement in recent pretreaments, metabolic engineering approaches with special emphasis on the latest developments in consolidated biomass processing, current global scenario of bioethanol pilot plants and biorefinery concept for the production of biofuels and bioproducts. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Consolidated biomass processing; Lifecycle assessment; Lignocellulose; Pre-treatment; Saccharifying enzymes; Value-added products

Approach towards biocatalytic valorisation of barley beta-glucan for bioethanol production using 1,3-1,4 beta-glucanase and thermotolerant yeast - Divate, Rupesh; Menon, Vishnu; Rao, Mala (International Biodeterioration & Biodegradation, 2013)
The exploitation of renewable resource containing polymers other than cellulose and hemicellulose are critically important for the feasibility of biofuel production. The potential of 1,3-1,4 glucan 4-gluconohydrolyase mediated saccharification of barley beta-glucan (BG) was investigated for ethanol production using thermotolerant Saccharomyces sp. A maximum hydrolysis of 71% was obtained in 24 h using in-house produced 1,3-1,4 beta-glucanase from an alkalothermophilic Thermomonospora sp. whereas the hydrolysis was 100% with Accellerase (TM) 1000. The synergistic effect of beta-glucosidase and 1,3-1,4 beta-glucanase was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora 1,3-1,4 beta-glucanase which resulted in complete hydrolysis of BG. The hydrolysates of BG obtained using Accellerase or a cocktail of Thermomonospora 1,3-1,4 beta-glucanase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.44 g g(-1) and 0.46 g g(-1) respectively and when fermented with immobilized cells produced a yield of 0.49 g g(-1). The Ca-alginate immobilized yeast cells were reused nine times at 40 degrees C with 100% fermentation efficiency. The economics of barley-to-fuel ethanol program will ameliorate if in addition to barley starch, beta-glucan is also utilized. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-1; 4 Glucan 4-gluconohydrolyase; Barley beta-glucan; Ethanol; Hydrolysis; Synergism; Thermotolerant yeast

Mechanistic insights into the inhibition of endo-beta 1,4 xyloglucan hydrolase by a classical aspartic protease inhibitor - Menon, Vishnu; Rao, Mala (Journal of Fluorescence, 2013)
This is the first report of inactivation of xyloglucanase from Thermomonospora sp by pepstatin A, a specific inhibitor towards aspartic proteases. The steady state kinetics revealed a reversible, competitive, two-step inhibition mechanism with IC (50) and K (i) values of 3.5 +/- 0.5 mu M and 1.25 +/- 0.5 mu M respectively. The rate constants determined for the isomerization of EI to EI* and the dissociation of EI* were 14.5 +/- 1.5 x 10(-5) s(-1) and 2.85 +/- 1.2 x 10(-8) s(-1) respectively, whereas the overall inhibition constant K (i) (*) was 27 +/- 1 nM. The conformational changes induced upon inhibitor binding to xyloglucanase were monitored by fluorescence analysis and the rate constants derived were in agreement with the kinetic data. The abolished isoindole fluorescence of o-phthalaldehyde (OPTA)-labeled xyloglucanase and far UV analysis suggested that pepstatin binds to the active site of the enzyme. Our results revealed that the inactivation of xyloglucanase is due to the interference in the electronic microenvironment and disruption of the hydrogen-bonding network between the essential histidine and other residues involved in catalysis.
Keywords: 4 xyloglucan hydrolase; Endo-beta 1; Enzyme kinetics; Inactivation mechanism; Pepstatin; Slow-tight binding

Interactions of a low molecular weight inhibitor from streptomyces sp. MBR04 with human cathepsin D: implications in mechanism of inactivation - Menon, Vishnu; Rao, Mala (Applied Biochemistry and Biotechnology, 2014)
Cathepsin D, a lysosomal aspartic protease, is of potential interest as a target for drug design due to its implication in breast and ovarian cancer. The article reports a low molecular weight cathepsin D inhibitor from Streptomyces sp. MBR04. The M-r of the inhibitor was 1,078 Da as determined by MALDI-TOF, and the amino acid analysis showed the presence of Asp, Asp, Gly, Ala, Lys, Leu, Tyr, Trp residues. The steady-state kinetic interactions revealed reversible, competitive, slow-tight-binding nature of the inhibitor with an IC50 and K (i) values of 3.2 and 2.5 nM, respectively. The binding of the inhibitor with the enzyme and the subsequent conformational changes were monitored by exploiting the intrinsic fluorescence of the surface exposed Trp-54 residue. Based on the fluorescence and circular dichroism studies, we demonstrate that the inhibitor binds to the active site of cathepsin D and causes inactivation. All these kinetic, thermodynamic, and quenching studies suggest that the newly isolated peptidic inhibitor could be a potential scaffold to study and can be used to develop new potent therapeutic lead molecule for the development of drugs. The inhibitor will be significant as a potential lead molecule to target cathepsin D.
Keywords: Cancer treatment; Cathepsin D inhibitor; Inactivation mechanism; Slow-tight-binding inhibition; Streptomyces sp MBR04